2017
DOI: 10.1186/s12967-017-1257-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 6-month pedometer-based walking intervention on functional capacity in patients with chronic heart failure with reduced (HFrEF) and with preserved (HFpEF) ejection fraction: study protocol for two multicenter randomized controlled trials

Abstract: BackgroundRegular physical activity is recommended for patients with chronic heart failure to improve their functional capacity, and walking is a popular, effective, and safe form of physical activity. Pedometers have shown potential to increase the amount of walking across a range of chronic diseases, but it is unknown whether a pedometer-based intervention improves functional capacity and neurohumoral modulation in heart failure patients.MethodsTwo multicenter randomized controlled trials will be conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 55 publications
1
22
1
1
Order By: Relevance
“…The present findings add to a growing body of evidence suggesting that lower levels of PA may independently associate with poor transplant clinical outcomes, independent of other psychosocial characteristics. Our findings extend previous work in pulmonary and cardiac samples demonstrating that lower levels of actigraphy‐assessed PA are predictive of poorer clinical outcomes. Our work also extends previous findings among lung transplant recipients by demonstrating that greater post‐transplant depressive symptoms also are associated with worse clinical outcomes, independent of PA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present findings add to a growing body of evidence suggesting that lower levels of PA may independently associate with poor transplant clinical outcomes, independent of other psychosocial characteristics. Our findings extend previous work in pulmonary and cardiac samples demonstrating that lower levels of actigraphy‐assessed PA are predictive of poorer clinical outcomes. Our work also extends previous findings among lung transplant recipients by demonstrating that greater post‐transplant depressive symptoms also are associated with worse clinical outcomes, independent of PA.…”
Section: Discussionsupporting
confidence: 86%
“…Recent case series data suggest that cardiothoracic transplant recipients exhibit lower levels of PA within 1 year of transplantation compared with age‐ and gender‐matched controls and that PA may be improved through intervention . In addition, lower levels of PA have been associated with poorer clinical outcomes in both pulmonary and cardiac patients. Although few studies have examined PA and related factors following transplant, we recently demonstrated that lower functional capacity (eg, six‐minute walk distance [6MWD]) was independently associated with worse clinical outcomes after lung transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…These patients were participants of an ongoing multicentre randomized controlled trial of a 6-month intervention in the form of an unsupervised, individual, outside walking programme that combined weekly step goals, selfmonitoring, and regular phone-based counselling, followed by a 6-month follow-up period. 6 As part of the intervention, the patients were requested to wear a wrist-worn accelerometer, and they were recommended to continue wearing it during the follow-up period and beyond. All patients, those still participating in the intervention and those in the follow-up phase and beyond, were included in this study, provided their accelerometer data were available.…”
Section: Methodsmentioning
confidence: 99%
“…(1) Limit the use of steps only to the studies that focus on walking, for example, when the aim of the intervention is to increase daily number of steps, or when participants are instructed to self-monitor their steps. 57 In addition, researchers and clinicians must be cognizant of the inaccuracy of most devices at slow gait speeds. 58 (2) Use time spent in PA intensity levels with caution, especially in patients with reduced cardiorespiratory fitness.…”
Section: Practical Recommendationsmentioning
confidence: 99%